Comparison between NI-SALICIDE and self-aligned lift-off used in fabrication of ohmic contacts for sic power MOSFET - Śledziewski, Tomasz; Erlbacher, Tobias; Bauer, Anton; Frey, Lothar; Chen, Ximing; Zhao, Yanli; Li, Chengzhan; Dai, Xiaoping (Materials Science Forum, 2019)
A comparison between self-aligned process (using lift-off) and Ni-SALICIDE (nickel self-aligned silicide) used in fabrication of ohmic contacts for SiC Power MOSFET is done. Both processes are demonstrated for 3.3 kV SiC VDMOS transistors fabricated on 100 mm substrates. It is shown that the Ni-SALICIDE process with first silicidation at 500°C does not degrade the electrical properties of silicon dioxide; particularly, a degradation of the interlayer dielectric between source and gate is not evident. Additionally, this first silicidation is found to have a positive impact on the specific resistance of contacts formed on p-type SiC using NiAl2.6% as an ohmic metal (ρc ≈ 400 µΩcm2).
CRIS-Team Scopus Importer:2019-09-17
Keywords: 4H-SiC; MOSFET; Nickel Silicide; Ohmic Contact; Salicide; Self-Alignment